2008
DOI: 10.1016/j.fertnstert.2007.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Placental expression profiling in preeclampsia: local overproduction of hemoglobin may drive pathological changes

Abstract: Using microarrays made with cDNAs from subtracted placental libraries, we show increased hemoglobin production in the preeclamptic placenta. Heme and hemoglobin may cause endothelial damage and inflammation and drive pathological changes in the placenta if they are released there. Study Objective:To create a library enriched in cDNAs from preeclamptic placentas to print on to microarrays for placental profiling of preeclampsia (PE) and high risk pregnancies. Design: Prospective study.Setting: University women'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
1
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 52 publications
3
85
1
2
Order By: Relevance
“…Hb-perfusion, in general, led to a massive up-regulation 23 of genes. The gene ontology-analyses showed that apoptosis-, oxidative stress-, and immune-related genes were frequently represented, confirming data from previously reported findings based on gene array studies on PE placentas [6,[47][48][49].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Hb-perfusion, in general, led to a massive up-regulation 23 of genes. The gene ontology-analyses showed that apoptosis-, oxidative stress-, and immune-related genes were frequently represented, confirming data from previously reported findings based on gene array studies on PE placentas [6,[47][48][49].…”
Section: Discussionsupporting
confidence: 88%
“…1). The PCR reactions were carried out in duplicates including negative controls (without template) in each run as previously described [6]. Gene transcript of the A1M gene was quantified using SYBR green in an iCycler Thermal Cycler (Bio-Rad Laboratories, Hercules, CA, USA) as previously described [20].…”
Section: Array Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…By gene expression microarray technology, it was recently shown that PE is associated with overexpression of the hemoglobin (Hb) subunits α2 and γ in the placenta [4]. Hb, the oxygen-carrying molecule in red blood cells, consists of four globin chains, each binding an iron-containing heme group.…”
Section: Introductionmentioning
confidence: 99%
“…HO-1 has antioxidative, anti-inflammatory and anti-apoptotic effects. Centlow et al, (2008) observed that placental tissue from preeclamptic women exhibited increased expression of Hb and Hb mRNA than placentas from normal pregnant women. Increased number of cells expressed Hb in the preeclamptic patients' placentas suggesting that either the cells were migrating into or out of the vessels or there may be binding sites on the vessel walls.…”
Section: Pregnancy Complications -Preeclampsiamentioning
confidence: 93%